Impact of Economic Policy Uncertainty on the Corporate Debt Maturity Structure: Evidence from the United Kingdom - Xing, Cheng (2020)
This academic paper intends to verify the connection between policy uncertainty and firm’s debt maturity structure in the domestic market of UK. The specific case is composed of UK listed non-financial firms from 2011 to 2018. Concerning the correlation between policy indeterminacy and firm’s debt maturity structure, two opposite perspectives could make an explanation. Whereas the demand-side hypothesis makes a positive forecast about a relationship between policy uncertainty and corporate debt maturity, as well as a supply-side hypothesis calculate the contrary. Using a fixed-effects variable coefficient model and a random-effects model, the study shows that UK companies apply more long-term debt within their debt organization when the degree of UK policy uncertainty is higher. The finding of this study for the UK market supports the demand-side hypothesis and is contrary to the previous finding for the US market. This paper believes that this is because the protection of creditor rights in the UK is different from that in the US. The strong creditor rights in the UK can help UK creditors provide long-term debt to UK corporates. The finding of this study is robust when it employs an instrumental variables technique to deal with endogeneity problems. Moreover, it shows that the positive relationship between policy indeterminacy and UK firms’ debt maturity exists only for companies with low default risk. Finally, this dissertation provides several recommendations to policymakers, investors, and researchers.